Mudanças nas representações territoriais socioambientais decorrentes da Itaipu Binacional - Abbade, Luciana Ferraz (2023)
On April 25, 1961, the National Congress approved the creation of Centrais Elétricas Brasileiras S/A – Eletrobrás, by Law No. 3890 (LIMA, p. 87). In this same period, a bold energy project was already being considered, using the power of the waters of the Saltos de Sete Quedas. Based on development in the energy sector and government support, the construction of the Itaipu hydroelectric plant created a new political, social and environmental scenario in Brazil. In view of the exposed scenario, the problem-question focused on: What are the changes in socio-environmental territorial representations arising from Itaipu Binacional. The specific objectives were: a) To describe the construction and operation process of Itaipu Binacional. b) Verify the existence of socio-environmental actions in the municipalities adjacent to the lake of Itaipu Binacional and, c) Identify the elements that make up the socio-environmental territorial representations. To this end, bibliographical surveys were carried out on the territory; representations; Power relations; territorial representations; territorialities; cartographic mapping, borders; limits, socio-environmental responsibilities, development of the energy sector, formation of the State of Paraná and also of the municipalities adjacent to the Itaipu lake. In the search for elements of socio-environmental territorial representations, data were collected from the statistical websites of the IBGE (@cidades) and also from iPardes, official platforms of the city halls of the municipalities adjacent to the Itaipu Lake reservoir, of the Development Council of the Lindeiros Municipalities to Lake Itaipu and mainly to the Entidade Itaipu Binacional, both on the Brazilian and Paraguayan shores. Since, from the website of the Entidade Itaipu Binacional, all official Annual Reports were analyzed, between the years 1974 to 2021.